2016
DOI: 10.1021/acs.jpcc.6b04964
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Oxygen Vacancies on Luminescence Properties of Na3LuSi3O9:Ce3+

Abstract: Oxygen vacancies play an important role in the luminescence processes of inorganic scintillator materials. In order to study the effects of oxygen vacancies on the luminescence properties of Na3LuSi3O9:Ce3+, these phosphors were prepared using a high temperature solid-state reaction method under different atmosphere and raw materials. It was found that oxygen vacancy had great influence on the absorption, photoluminescence and decay curves of Na3LuSi3O9:Ce3+. The luminescence intensity and peak position showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…The shallow peaks (330 K) in the Ca 3 Ga 4 O 9 :Bi 3+ phosphor were assigned to intrinsic traps due to their similar position with the trap at 326 K in the Ca 3 Ga 4 O 9 host. The extra deep traps (470–600 K) may be attributed to the inequivalent substitution of Bi 3+ for Ca 2+ (BiCa) in accordance with reported examples of Binormalk, DySr, and TiNa . Interestingly, when Bi2 was excited using 365 nm, the deep trap regions were mainly filled, especially the extra deep trap region ( Figure e).…”
Section: Resultssupporting
confidence: 86%
“…The shallow peaks (330 K) in the Ca 3 Ga 4 O 9 :Bi 3+ phosphor were assigned to intrinsic traps due to their similar position with the trap at 326 K in the Ca 3 Ga 4 O 9 host. The extra deep traps (470–600 K) may be attributed to the inequivalent substitution of Bi 3+ for Ca 2+ (BiCa) in accordance with reported examples of Binormalk, DySr, and TiNa . Interestingly, when Bi2 was excited using 365 nm, the deep trap regions were mainly filled, especially the extra deep trap region ( Figure e).…”
Section: Resultssupporting
confidence: 86%
“…All these spectra exhibit a similar tendency except the Sc/Mo 5:1; it clearly shows an extra intense absorption band centered at about 3.85 eV (322 nm), which is mainly caused by oxygen vacancies. In fact, similar phenomena have also been reported by Zhou et al where the absorption band is observed at 320 nm . Combining the experimental observation and the DFT calculation, we can conclude that the theoretical E gap value 3.56 eV corresponded to the experimental value of 3.69–4.16 eV, as it is generally accepted that the DFT calculation at LDA level has an underestimation.…”
Section: Resultssupporting
confidence: 90%
“…In fact, similar phenomena have also been reported by Zhou et al where the absorption band is observed at 320 nm. 36 Combining the experimental observation and the DFT calculation, we can conclude that the theoretical E gap value 3.56 eV corresponded to the experimental value of 3.69−4.16 eV, as it is generally accepted that the DFT calculation at LDA level has an underestimation.…”
Section: Resultssupporting
confidence: 63%
“…Meanwhile, for the phosphate material, there are many reports about the occurrence of oxygen vacancies through oxygen escaping from sites during the sintering process under both reducing and air atmospheres. 36 As a result, numerous traps may exist to capture electrons or holes in the host. Fig.…”
Section: Resultsmentioning
confidence: 99%